The California adverse childhood experiences screening roll-out: a survey study of ACEs screening implementation in primary care - Clare Viglione; Clare Viglione; Clare Viglione; Kathleen Soon; Sandra Wittleder; Kyung E. Rhee; Renée Boynton-Jarrett; Pradeep Gidwani; Blanca Melendrez; Eric Hekler; Eric Hekler (Frontiers in Public Health)
BackgroundCalifornia adopted universal screening of adverse childhood experiences (ACEs) in January 2020 and dedicated significant financial and human resources to “ACES Aware,” a statewide campaign to scale ACEs screening throughout the state. Provider perspectives after the roll-out of ACEs Aware have been understudied. The aim of this study was to understand provider perspectives on universal ACEs screening in primary care. We explored indicators of acceptability, utility, and barriers and facilitators of screening for ACEs. We also investigated treatments offered for disclosed ACEs.MethodsA cross-sectional survey with quantitative and qualitative components was distributed via Facebook, Twitter, and electronic listservs between March and April 2022, 2 years after the launch of ACEs Aware. The survey included the validated and reliable “Acceptability of Implementation Measure” and “Feasibility of Implementation Measure” as well as multiple choice, ranking, and free-text items to understand determinants of screening and treatment approaches.ResultsEighty two primary care providers in California, working primarily in pediatrics (84%), completed the survey. The majority (78%) received training on assessing ACEs and 60% reported using the Pediatric ACEs and Related Life-events Screener (PEARLS). About 22% “strongly agree” that PEARLS is acceptable and 32% “strongly agree” that PEARLS is feasible. Only 17% “strongly agree” that they like PEARLS. The top barriers were: (1) insufficient time; (2) unclear treatment pathway for detected ACEs; and (3) inadequate staffing to perform screening. The top facilitators for screening were: (1) financial incentives for providers to screen; (2) financial incentives for organizational leadership to implement screening; and (3) leadership support of screeners. The top approaches for addressing ACEs were: (1) behavioral therapy; (2) case navigation; and (3) trauma-informed care.ConclusionThis study provided a first look at provider perspectives on ACEs screening and treatment in a sample of California providers. Most responding providers report currently screening for ACEs and using PEARLS. Perceptions of feasibility were slightly higher than for acceptability. Facilitators were largely top-down and organizational in nature, such as financial incentives and leadership support. Future directions could include an exploration into why some providers may find ACEs unappealing and research to identify effective and accessible treatment approaches for ACEs.